2015
DOI: 10.1142/s0192415x15500214
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic Acid Reverses the Cognitive Dysfunction Caused by Amyloid β Peptide 1-40 Through Anti-Oxidant Activity and Cholinergic Activation in Rats

Abstract: Cholinergic dysfunction and oxidation stress are the dominant mechanisms of memory deficit in Alzheimer's disease (AD). This study describes how ferulic acid (FA) ameliorates cognitive deficits induced by mecamylamine (MECA), scopolamine (SCOP), central acetylcholinergic neurotoxin ethylcholine mustard aziridinium ion (AF64A) and amyloid β peptide (Aβ1-40). This study also elucidates the role of anti-oxidant enzymes and cholinergic marker acetylcholinesterase (AChE) in the reversal of FA from Aβ1-40-induced co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 40 publications
(79 reference statements)
1
18
0
1
Order By: Relevance
“…Caffeic acid attenuated tau phosphorylation by the reduction of GSK-3β activation against Aβ-induced neurotoxicity (Sul et al, 2009). Quercetin, chlorogenic acid, and ferulic acid have been shown to protect cognitive dysfunction and neuronal damage in several experimental models by inhibiting apoptosis, oxidative stress, autophagy, and inflammation, underlying pathways of AD-like pathological condition (Joseph et al, 2010;Sabogal-Guáqueta et al, 2015;Tsai et al, 2015). We hypothesize that the multiple bioactive effects of ME on neuroassociated models and its various phytochemicals contributed to the neuroprotective effect observed in the present study.…”
Section: Discussionsupporting
confidence: 53%
“…Caffeic acid attenuated tau phosphorylation by the reduction of GSK-3β activation against Aβ-induced neurotoxicity (Sul et al, 2009). Quercetin, chlorogenic acid, and ferulic acid have been shown to protect cognitive dysfunction and neuronal damage in several experimental models by inhibiting apoptosis, oxidative stress, autophagy, and inflammation, underlying pathways of AD-like pathological condition (Joseph et al, 2010;Sabogal-Guáqueta et al, 2015;Tsai et al, 2015). We hypothesize that the multiple bioactive effects of ME on neuroassociated models and its various phytochemicals contributed to the neuroprotective effect observed in the present study.…”
Section: Discussionsupporting
confidence: 53%
“…Inhibition of AChE has been used as a therapeutic strategy for Alzheimer's disease and other types of dementia (Lle o et al 2006). The previous study demonstrated that FA could reverse the cognitive deficits caused by Ab 1-40 though suppress AChE activity in rats with a dose-dependent manner (Tsai et al 2015). We also found that the high activity of AChE in D-gal-treated mice brain could be notably inhibited by chronic administration of FA (100 mg/kg), but it could not be significantly inhibited by lower dose of FA (50 mg/kg), which maybe one of the reasons that the study results of Yan et al (2001) showed no significant difference.…”
Section: Discussionmentioning
confidence: 96%
“…Our study confirmed using Pearson's correlation analysis that oxidative damage in the brain contributes to the spatial memory deficit in D-gal-treated mice. FA, a small molecule phenolic acid, can transport across the blood-brain barrier and ameliorated oxidative stress induced by Ab 1-40 which might be attributed to the hydroxyl group on the benzene ring (Barone et al, 2009;Wu et al 2014;Tsai et al 2015). It indicates that FA possesses protective effect against oxidative stress in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…FA was shown to directly inhibit the memory impairment of Aβ1-40 induced AD in rats while reversing the deterioration of anti-oxidative factors. FA also rescued the compromised acetylcholine esterase activity characteristic of the AD phenotype [98]. These effects are likely administered by the combined anti-inflammatory, anti-oxidative and enhanced choline acetyltransferase activity of FA [99].…”
Section: Ferulic Acidmentioning
confidence: 89%